2011
DOI: 10.1080/10503307.2011.592550
|View full text |Cite
|
Sign up to set email alerts
|

Counseling activity in single-session online counseling with adolescents: An adherence study

Abstract: While online counseling is increasingly utilized, little is known about what counseling work takes place in the online environment. The aim of this study was to quantify online counseling activity by determining counselors' adherence to the widely used model in which they had been trained. Transcripts (n=85) of online counseling with adolescents were evaluated, using a standardized and psychometrically sound instrument. We found that, while counseling in 53% of transcripts progressed through each of the key st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 17 publications
1
37
0
1
Order By: Relevance
“…Still, the high number of missing values indicates a suboptimal helpline practice with volunteers not focusing enough on suicidality at the beginning and the end of the conversation. This problem, which has been highlighted by studies examining telephone crisis services (Coveney et al., ; Gould et al., , ; Kalafat et al., ; Mishara et al., ), may be even more prominent for crisis chats that are known to drift toward exploration of problems more than toward their solution (Bambling, King, Reid, & Wegner, ; Chardon, Bagraith, & King, ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, the high number of missing values indicates a suboptimal helpline practice with volunteers not focusing enough on suicidality at the beginning and the end of the conversation. This problem, which has been highlighted by studies examining telephone crisis services (Coveney et al., ; Gould et al., , ; Kalafat et al., ; Mishara et al., ), may be even more prominent for crisis chats that are known to drift toward exploration of problems more than toward their solution (Bambling, King, Reid, & Wegner, ; Chardon, Bagraith, & King, ).…”
Section: Discussionmentioning
confidence: 99%
“…These modalities differ with respect to their advantages and disadvantages (Mora, Nevid, & Chaplin, 2008). The most common modality for online therapy, that is, textbased e-mail, is asynchronous, meaning that participants typically respond to one another when they have time, whereas they respond immediately in synchronous text chat and audio or videoconference (Chardon, Bragraith, & King, 2011). Synchronous communication allows for a more spontaneous and immediate interaction because the therapist may provide a timely answer to the client's requests.…”
Section: Introductionmentioning
confidence: 99%
“…Content analysis of the emails showed that the techniques were not applied to their full potential, and the realisation factor of the GEP model, comprising 10 empowerment-oriented techniques, was modest in both groups. Similarly, Chardon et al (2011) found a low level of realisation of counselling components in single session online consultation with adolescents, specifically in the guidance towards setting goals and planning actions. This raises the question whether it is feasible to apply a rich, but rather complex model for consultative practice in a brief textual advice.…”
Section: Discussionmentioning
confidence: 97%
“…Empirical studies on SSEC are scarce (Chardon, Bagraith, & King, 2011;Cornwall, Moore, & Plant, 2008;Richards, 2009) and not situated in a parenting support context. In order to distinguish its functions, it is useful to investigate the related body of scholarly literature on both online counselling and single-session treatment, which has developed over the last decades.…”
Section: Online and Single Sessionmentioning
confidence: 98%